THE EFFECT OF HEALTH EDUCATION WITH VIDEOS AND FLASH CARDS ON KNOWLEDGE AND SKILLS OF FETAL STIMULATION IN PREGNANT WOMEN - Arista Apriani; Wijayanti Wijayanti; Deny Eka Widyastuti; Yunia Renny Andhikatias; Megayana Yessy Mareta (Gaster, 2022)
Integrated antenatal care is a comprehensive and quality health service, one of which is through the provision of health services and counseling, including stimulation so that the pregnancy is healthy and the fetus is born healthy and smart. Health education is communication designed to increase knowledge, life skills that are conducive to individual and community health, foster the motivation, and confidence needed to take action to improve health. The purpose of this study was to determine the effect of health education using video and flashcard media compared to lectures on the level of knowledge and skills of pregnant women to stimulate the fetus. This research was conducted in February – July 2021 at the Jaten I Health Center in the Work Area of the Karanganyar District Health Office. This type of quasi-experimental research (before and after with control experiment design). The sampling technique was purposive with a total of 15 for each group. Data analysis with multiple linear regression (ANACOVA). The conclusion is that there is an effect of early stimulation of fetal growth and development on the knowledge and skills of pregnant women to stimulate the fetus with the results of the knowledge score of the experimental group being 5.15 points higher than the control group (b = 5.51; 95% CI; 4.34 to 5. 96; p < 0.001). Adjusted R2 = 89.8%. And the experimental group had skills 11.82 points higher than the control group (b = 11.82; 95% CI; 8.04 to 15.60; p < 0.001). Adjusted R2 = 59.9% by controlling for formal education level and scores before treatment.